(untitled) (Research, Society and Development, 2023)
The use of psychoactive substances, especially alcohol, has been stimulated through consumer society models that are exposed in ads, digital media, movies, advertising videos and song lyrics. In recent years, alcohol consumption among medical students has increased considerably. This paper aims to describe the pattern of alcohol use by students at a private college. This is a quantitative, cross-sectional and descriptive study. Data collection was carried out with 360 students, from the 1st to the 12th period, of the medical course at a Private Faculty in Teresina, Piauí. The questionnaires received were recorded in a Microsoft Excel spreadsheet, which was later exported to IBM SPSS and Statistics 20.0. The answers to the AUDIT test were revealing, as they showed an increase of more than 23% in alcohol consumption among university students when they entered the medical course, a 54.9% increase in the frequency of alcohol use at parties at the private college and 34.3% in the pre and post test periods. The data revealed the increased consumption of alcohol observed in the increased frequency of alcohol use at parties at the private college, as well as in the pre- and post-test periods. The data show the overconfidence about alcohol consumption among university students and the lack of knowledge about the addictive power of alcohol abuse. More research is needed to analyze the consequences of alcohol abuse by students.